Evaluation of nootropic and neuroprotective properties of Siddha drug Poorana Chandrothaya Chenthuram (PCC) in scopolamine-induced amnesia in mice - Chitra Balasubramanian; R S Ramaswamy (Elsevier, 2024)
Background: Poorana Chandrothaya Chenthuram (PCC) is a gold-based Siddha drug, for treating diverse diseases. Rooted in centuries-old traditional use, Siddha texts categorize PCC as a kayakarpa entity that emphasizes holistic well-being. Aim: This study assesses the nootropic potential of Poorana Chandrothaya Chenthuram (PCC) in scopolamine-induced amnesic mice, and elucidate the underlying mechanisms, specifically focusing on the modulation of cholinergic system and anti-oxidant effects. Methods: Preliminary finger printing with FTIR was done. Scopolamine-induced memory impaired mice were administered PCC (15 or 30 mg/kg) for 28 days. Memory assessments were done using elevated plus-maze and passive avoidance tasks. RT-PCR gauged mRNA expression levels of AChE, MChR, BAX, and BCL2 in brain samples were also done. Results: FTIR confirmed the presence of functional groups in PCC. In the EPM test, pre-treatment with PCC (15 and 30 mg/kg) significantly reduced the time taken (p < 0.05 and 0.01, respectively), comparable to the reference control, piracetam. The PAT revealed a significant increase (p < 0.01) in the time taken to step down from the escape platform which demonstrates that significant efficacy in reversing scopolamine-induced amnesia in mice. Gene expression studies reported a significant up-regulation (p < 0.01) in AChE, MChR, and BAX mRNA expressions, along with a down-regulation in BCL2 expression compared to normal mice. Conclusion: This study demonstrates the anti-amnesic activity of the Siddha drug PCC, elucidating its mechanism involving a reduction in AChE levels and an augmentation of antioxidant levels in which implicates modulation of cholinergic and apoptotic pathways. In-depth exploration of PCC's neuroprotective properties may unveil novel avenues for combating memory and cognitive decline.